TARGET2 analytical tools for regulatory compliance - Marc Glowka; Alexander Müller; Livia Polo Friz; Sara Testi; Massimo Valentini; Stefano Vespucci (European Central Bank (ECB), 2022)
As the operator of a systemically important payment system (SIPS), the Eurosystem has the responsibility of regularly assessing the resilience of the Trans-European Automated Real-time Gross Settlement Express Transfer System (TARGET2) to various types of risks, as set out in the Principles for Financial Market Infrastructures (PFMIs) drawn up by the Committee on Payments and Market Infrastructures (CPMI) and International Organization of Securities Commissions (IOSCO). To identify, measure, monitor and mitigate these risks over time, the TARGET2 operator has developed specific approaches that include both qualitative and quantitative elements. The paper offers a comprehensive overview of the quantitative tools developed and used by the TARGET2 operator, through the TARGET Analytics Group (TAG), to support the risk assessment processes required to comply with the PFMIs. The toolkit is based on transaction-level data analysis and ranges from individual statistical indicators to more complex methodologies using advanced analytics and specific tools, such as the TARGET2 simulator. Since all major payment systems worldwide are required to comply with the PFMIs, this topic is of interest to the relevant operators and oversight bodies around the globe. Moreover, although mainly developed for regulatory compliance purposes, these indicators and studies offer important insights into traffic patterns, system efficiency, usage of different system features, liquidity flows, the behaviour of individual participants and their interconnections
Keywords: G20; E42; E58; C10; C63; 330; payment systems; TARGET2; FMIs; PFMIs